1998
DOI: 10.1093/humrep/13.11.3144
|View full text |Cite
|
Sign up to set email alerts
|

Routine addition of human insulin-like growth factor-I ligand could benefit clinical in-vitro fertilization culture

Abstract: Animal studies suggest that the insulin-like growth factors play an important role in preimplantation embryo development. Human preimplantation embryos express mRNA for insulin-like growth factor-I receptor (IGF-IR) but the ligand, insulin-like growth factor-I (IGF-I), is not expressed by the embryo until after implantation. We tested the hypothesis that IGF-I produced by the female reproductive tract may bind to these receptors, augmenting embryo survival, growth and development. Transcripts of mRNA for IGF1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
75
0
12

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(93 citation statements)
references
References 36 publications
6
75
0
12
Order By: Relevance
“…This is consistent with previous studies that showed a selective increase of cells in the ICM in bovine blastocysts (Sirisathien et al 2003) and embryos from other species treated with IGF1, including humans (Lighten et al 1998), pigs (Kim et al 2005) and mice (Smith et al 1993). The localised cell proliferation seems to be related to activation of the MAPK pathway in the ICM by IGF1 (Navarrete Santos et al 2008).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is consistent with previous studies that showed a selective increase of cells in the ICM in bovine blastocysts (Sirisathien et al 2003) and embryos from other species treated with IGF1, including humans (Lighten et al 1998), pigs (Kim et al 2005) and mice (Smith et al 1993). The localised cell proliferation seems to be related to activation of the MAPK pathway in the ICM by IGF1 (Navarrete Santos et al 2008).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the amino acid sequence of bovine IGF1 is identical to that of human IGF1 (Honegger & Humbel 1986, Francis et al 1988. In both the species, supplementation with physiological concentrations of human recombinant IGF1 can exert positive effects on in vitro preimplantation embryo development (Lighten et al 1998, Spanos et al 2000, Byrne et al 2002, Makarevich & Markkula 2002.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, proportion of M II oocytes were significantly (P<0.05) increased by IGF-1 supplementation at normal temperature condition (38.5°C) compared to the other groups. Stimulatory effect of IGF-1 on oocyte maturation and further embryo development is well established [14,20]. Also, it has been established that IGF-1 has a beneficial effect on oocyte nuclear maturation [21,22], whereas, oocyte expresses IGF-1 receptor [23].…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of apoptosis by means of using well known anti-apoptotic factors such as IGF-1 [9][10][11][12] may be a useful tool for decreasing the deterioration effects of heat stress on oocyte developmental competence. Insulin like grow factor-1 is a potent stimulator of oocyte maturation and subsequent embryonic development [13,14] and is a suppressor of apoptosis [13,15]. For the current experiments, it was hypothesized that the presence of IGF-1 during in vitro maturation (IVM) as an anti-apoptotic factor can improve bovine oocyte developmental competence under heat stress.…”
Section: Introductionmentioning
confidence: 99%